1997
DOI: 10.1017/s0952523800011755
|View full text |Cite
|
Sign up to set email alerts
|

Hyperstriatum ventrale in pigeons: Effects of lesions on color-discrimination and color-reversal learning

Abstract: Previous lesion studies of color-reversal learning in pigeons show that an impairment results when (1) the tectofugal visual pathway is damaged at either the thalamic level (nucleus rotundus) or the telencephalic level (ectostriatum), or (2) the thalamofugal visual pathway is damaged at the telencephalic level (the visual Wulst). An impairment does not result, however, when the thalamic source of thalamofugal input (n. opticus principalis thalami or OPT) to the visual Wulst is damaged. These results suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
3
8
0
Order By: Relevance
“…M, formerly known as hyperstriatum ventral (HV) (Reiner et al 2004a), is a telencephalic region, part of the avian pallium (Reiner et al 2004a). Previous studies associated M with color discrimination in pigeons (Chaves and Hodos 1997) while HV relative size was found to significantly correlate with the rate of feeding innovation in birds (Timmermans et al 2000). In primates, a similar correlation was observed with the relative size of the neocortex (Timmermans et al 2000;Michael et al 2015).…”
Section: Discussionsupporting
confidence: 57%
“…M, formerly known as hyperstriatum ventral (HV) (Reiner et al 2004a), is a telencephalic region, part of the avian pallium (Reiner et al 2004a). Previous studies associated M with color discrimination in pigeons (Chaves and Hodos 1997) while HV relative size was found to significantly correlate with the rate of feeding innovation in birds (Timmermans et al 2000). In primates, a similar correlation was observed with the relative size of the neocortex (Timmermans et al 2000;Michael et al 2015).…”
Section: Discussionsupporting
confidence: 57%
“…3 and 4). These telencephalic areas have been shown to form a neural circuit critical for audiovisual imprinting and passive avoidance learning in chicks (Horn, 1981; Horn, 2004; Cipolla-Neto, Horn & McCabe, 1982; Nakamori et al, 2010; Town & McCabe, 2011) and for colour-discrimination learning in pigeons (Chaves & Hodos, 1997) (though neither species present PGCs).…”
Section: Resultsmentioning
confidence: 99%
“…However, the critical period for imprinting in chicks ends approximately 1 week after hatching (Bolhuis, 1991; Maekawa et al, 2007) and whether activation of the mesopallium and nidopallium still has the same effect in the adult is unknown. Chaves and Hodos (1997) reported that the medial mesopallium engages in color discrimination in adult pigeons. It is therefore speculated that the structural organization for imprinting in IMM is still maintained in adults and that new functions other than imprinting are added.…”
Section: Discussionmentioning
confidence: 99%